REAKTUALISASI TERM AL-IKHWAH MELALUI PEACE EDUCATION GUNA MERESPON RASISME DALAM DUNIA PENDIDIKAN - Neneng Rumsiti; M Muslimah (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2021)
The main objective of this research is to examine more deeply about: (1) the causes and effects of the phenomenon of racism, (2) explore the meaning of the term al-ikhwah as the basis for the solution of the Qur'an to the problem of racism, and (3) an overview of the re-actualization of the concept of al-Ikhwah. -Ikhwah through peace education. The method used is a qualitative method approach with a concept analysis approach. The results of the study show that: (1) the main causes of racism that most often occur are the elements of fanaticism and egocentrism that are so excessive, that they view other races or ethnic groups as inferior to their group. (2) The meaning of al-ikhwah contained in the QS. Al-Hujurat [49]:10 contains the meaning of brotherhood based on solidarity and efforts to avoid disputes. (3) The actualization of the term al-ikhwah combined through peace education can be implemented in washatiyyah-based learning or moderate learning and build community culture in educational institutions that support a caring mentality.Keywords: Racism, Al-Ikhwah, Peace Education